Gold Nanoparticles Synthesized with Common Mullein (Verbascum thapsus) and Castor Bean (Ricinus communis) Ethanolic Extracts Displayed Antiproliferative Effects and Induced Caspase 3 Activity in Human HT29 and SW480 Cancer Cells - Karen M. Soto; Ivan Luzardo-Ocampo; José M. López-Romero; Sandra Mendoza; Guadalupe Loarca-Piña; Eric M. Rivera-Muñoz; Alejandro Manzano-Ramírez (MDPI AG, 2022)
Gold nanoparticles (AuNPs) are promising nanomaterials exhibiting anti-cancer effects. Green AuNPs synthesis using plant extracts can be used to achieve stable and beneficial nanoparticles due to their content of bioactive compounds. This research aimed to synthesize and evaluate the antiproliferative and caspase-3 activity induction of green AuNPs synthesized with common mullein (V. thapsus) flowers (AuNPsME) and castor bean (R. communis) leaves (AuNPsCE) ethanolic extracts in human HT29 and SW480 colorectal cancer cells. Their effect was compared with chemically synthesized AuNPs (AuNPsCS). The extracts mainly contained p-coumaric acid (71.88-79.93 µg/g), ferulic acid (19.07-310.71 µg/g), and rutin (8.14-13.31 µg/g). The obtained nanoparticles presented typical FT-IR bands confirming the inclusion of polyphenols from V. thapsus and R. communis and spherical/quasi-spherical morphologies with diameters in the 20.06-37.14 nm range. The nanoparticles (20-200 µg/mL) showed antiproliferative effects in both cell lines, with AuNPsCE being the most potent (IC50 HT29: 110.10 and IC50SW480: 64.57 µg/mL). The AuNPsCS showed the lowest intracellular reactive oxygen species (ROS) generation in SW480 cells. All treatments induced caspase 3/7 activity to a similar or greater extent than 30 mM H2O2-treated cells. Results indicated the suitability of V. thapsus and R. communis extracts to synthesize AuNPs, displaying a stronger antiproliferative effect than AuNPsCS.